Trends and Drivers of Inequality: Recent Evidence from Vietnam - Trang Huyen Dang; Cuong Viet Nguyen; Tung Duc Phung (Global Labor Organization (GLO), 2022)
This study provides evidence on the trends and drivers of inequality in Vietnam using Vietnam Household Living Standard Surveys. We find that inequality, regardless of the choice of welfare indicators and inequality measurements, has been stable in Vietnam. Inequality in income or expenditure is remarkably lower than inequality in assets. In 2016, the Gini coefficient of per capita expenditure and per capita income was 0.35 and 0.39, respectively, while the Gini coefficient in electricity consumption and housing value was 0.42 and 0.62, respectively. Using the decomposition analysis, we find that inequality between provinces accounts for 22% of the total inequality, while inequality between ethnic groups accounts for 15% of the total inequality. The regression analysis shows that inequality tends to be higher in provinces with higher initial income and poverty. This implies that high-income people are more likely to benefit from economic growth, especially in better-off provinces.
Keywords: F14; F15; I31; I32; 330; Economic integration; poverty; inequality; Vietnam